A Hidden Plague: Violence and Public Health in Colonial Guatemala City. (May 2022) - Sellers-García, Sylvia
How do colonial scribal practices and archival practices shape our understanding of the past? Logbooks from the San Juan de Dios Hospital in colonial Guatemala showcase both the potential and the constraints of scribal interventions. A Hidden Plague examines the logbooks alongside contemporary criminal cases to demonstrate how individual scribes chose to conceal or reveal information in their official writings. This method challenges the contention by past scholarship that epidemic disease was the greatest health threat to women in the city of Guatemala. While epidemics did indeed affect women, reading the logbooks in new ways reveals the presence of a hidden epidemic: domestic violence.